Translocating Wild California Valley Quail to Texas: An Evaluation of Survival, Dispersal, Tracking Efficacy, and Roost Preference - Garrett Rushing; Jordan T. Conley; Jeffrey G. Whitt; Kelly S. Reyna (National Quail Symposium Proceedings, 2022)
Quail translocations are becoming increasingly popular in regions of suitable habitat where local quail populations have declined. In northeastern Texas, USA, northern bobwhite (Colinus virginianus) populations have drastically declined for over a century and have reached undetectable levels in many areas. As a result, the number of quail hunters and quail conservation funding have also declined. California valley quail (Callipepla californica; hereafter, valley quail) have increased across their range and have been translocated to many states and countries. Thus, the goal of this study was to determine whether translocating wild valley quail to Texas was feasible, and evaluate their survival, dispersal, roost location preference, and potential predator impacts. We translocated 748 wild valley quail from Idaho, USA to northeastern Texas in 2019 and 2020. We collected quail location data from very high frequency (VHF) and digital transmitters. Motion-triggered cameras, scent stations, simulated nests, and raptor transects were used to record predator presence and potential predator impacts. Survival of birds with tracking devices was 63% (VHF) in 2019, and 38.8% (VHF) and 92.5% (digital tag) in 2020. Survival was greater for quail with digital transmitters. Median dispersal distance was 633.5 m in 2019 and 246.6 m in 2020 for valley quail with VHF transmitters, and 310.4 m for quail with digital transmitters. Minimum convex polygon area medians were 4.3 ha in 2019 and 3.1 ha in 2020 for quail with VHF transmitters, and 16.1 ha in 2020 for quail with digital transmitters. Roost sites were primarily in young stands of oak trees. Median simulated nest survival was 2 days (minimum [min] = 1, interquartile range [IQR] = 2–5.4, maximum [max] = 23) in 2019, and 7.5 days (min = 2, IQR = 4.5–15.2, max = 23) in 2020. The most frequent mammalian predators observed were raccoons (Procyon lotor), feral hogs (Sus scrofa), and white-tailed deer (Odocoileus virginianus). Red-tailed hawks (Buteo jamaicensis) were the most frequent aerial predator. We completed the first documented translocation of wild California valley quail to Texas, demonstrating it is feasible. Future translocation may benefit from translocating more birds over a longer period of time, with more consistent methodology. The establishment of a sustainable population may require ≥7 years of translocation at a rate of 500 birds per year with >2,000 ha of suitable habitat.
Keywords: California quail; Valley quail; Callipepla californica; translocation; Texas; radio telemetry; survival; dispersal; nest camera; nest predation; meso-mammal; predator-prey; scent stations; northern bobwhite; Colinus virginianus